The Correlation of the Limitations of Movement of the Shoulder Joint with the Functional Ability of Frozen Shoulder Patients at the Medical Rehabilitation Institute Dr. Mohammad Hoesin Palembang - Ine Sintia; Nyimas Fatimah (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background: Frozen shoulder is a condition of the shoulder joint that experiences inflammation, pain, adhesions, atrophy and shortening of the joint capsule resulting in limited motion. In frozen shoulder patients, the limited range of motion of the shoulder joint can affect and reduce functional ability. This study aims to analyze the correlation between the limited area of motion of the shoulder joint with the functional ability of frozen shoulder patients at the Medical Rehabilitation Installation Dr. Mohammad Hoesin Palembang. Methods: This study was an observational analytic study, correlation test, with a cross sectional design. There were 29 frozen shoulder patients who met the inclusion criteria in the Medical Rehabilitation Installation Dr. Mohammad Hoesin Palembang in November 2018 was taken as a sample using consecutive sampling techniques. Functional ability was assessed using the quickDASH questionnaire and the area of motion was measured using a goniometer, then analyzed. Results: The results of the correlation test showed significant results between functional abilities and the area of motion of the shoulder joints. Active flexion (p = 0.000; r = -0.669), active extension (p = 0.004; r = -0.520), active abduction (p = 0.000; r = -0.663), active adduction (p = 0.022; r = -0.423 ), passive flexion (p = 0.001; r = -0.589), passive extension (p = 0.002; r = -0.543), passive abduction (p = 0.000; r = -0.676), passive adduction (p = 0.038; r = -0.388). Conclusion: There is a significant correlation between limited joint motion and functional ability in frozen shoulder patients at the Medical Rehabilitation Installation of Dr. Mohammad Hoesin Palembang.